2021
DOI: 10.1093/bioinformatics/btab041
|View full text |Cite
|
Sign up to set email alerts
|

Robust gene coexpression networks using signed distance correlation

Abstract: Motivation Even within well studied organisms, many genes lack useful functional annotations. One way to generate such functional information is to infer biological relationships between genes/proteins, using a network of gene coexpression data that includes functional annotations. However, the lack of trustworthy functional annotations can impede the validation of such networks. Hence, there is a need for a principled method to construct gene coexpression networks that capture biological inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 33 publications
0
39
0
Order By: Relevance
“…For instance, Pardo-Diaz et al. ( 66 ) recently presented a novel method that adds directionality into the co-expression network. Finally, while we constructed a human interactome network from multiple pathway and interaction databases, the majority of proteins from the co-expression networks could not be mapped to the network, highlighting the incompleteness of the current interactome.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Pardo-Diaz et al. ( 66 ) recently presented a novel method that adds directionality into the co-expression network. Finally, while we constructed a human interactome network from multiple pathway and interaction databases, the majority of proteins from the co-expression networks could not be mapped to the network, highlighting the incompleteness of the current interactome.…”
Section: Discussionmentioning
confidence: 99%
“…Distance correlation values with p>0.01 were set to zero keeping only the most statistically significant correlations. Sign of distance correlation was equated to the sign of Pearson correlation calculation as shown by 16 and implemented in-house as: . Calculations we performed using Matlab in-house routing.…”
Section: Methodsmentioning
confidence: 99%
“…Distance correlation was developed by Székely et al 15 , as a measure of dependence between variables including linear and non-linear correlations as well as correlation between vectors of different lengths. Additionally, applications of distance correlation in genomics have shown that although distance correlation calculation provides only positive values, it is possible to use sign measure from Pearson’s correlation for the determination of signed distance correlation measure 16 . In addition to correlation network development, methods from clustering can provide alternative approaches for interaction or dependence network determination.…”
Section: Introductionmentioning
confidence: 99%
“…A full worked example can be found in Supplementary Section S5 and in the COGENT tutorial. COGENT has also been used to assess signed distance correlation as a measure of gene co-expression ( Pardo-Diaz et al , 2021 ). This application further shows that network construction methods prioritized by COGENT also capture more protein–protein interaction data than methods which were not prioritized.…”
Section: Applicationmentioning
confidence: 99%